2008
DOI: 10.1038/oby.2008.424
|View full text |Cite
|
Sign up to set email alerts
|

TOF‐SIMS Analysis of Lipid Accumulation in the Skeletal Muscle of ob/ob Mice

Abstract: Skeletal muscle lipid accumulation is associated with several chronic metabolic disorders, including obesity, insulin resistance (IR) and type 2 diabetes. The aim of this study is to evaluate whether static imaging time‐of‐flight‐secondary‐ion mass spectrometry (TOF‐SIMS) equipped with a Bismuth‐cluster ion source can be used for studying skeletal muscle lipid accumulation associated with obesity. Mouse gastrocnemius muscle tissues in 10‐week‐old obese ob/ob (n = 8) and lean wild‐type C57/BL6 (n = 6) mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 45 publications
(49 reference statements)
2
39
0
Order By: Relevance
“…A pulsed 25 keV Bi þ primary ion source (average current: 1.0 pA; pulse width: 12.1 ns; and repetition rate 100 mHz) was used over a 500 mm  500 mm area at an operating pressure of B1  10 À 9 mbar. Negative-ion profiles were recorded and analysed; this technique is ideally suited to searching for possible correlations related to the ejected secondary ion polarity of C and O atoms 51 .…”
Section: Methodsmentioning
confidence: 99%
“…A pulsed 25 keV Bi þ primary ion source (average current: 1.0 pA; pulse width: 12.1 ns; and repetition rate 100 mHz) was used over a 500 mm  500 mm area at an operating pressure of B1  10 À 9 mbar. Negative-ion profiles were recorded and analysed; this technique is ideally suited to searching for possible correlations related to the ejected secondary ion polarity of C and O atoms 51 .…”
Section: Methodsmentioning
confidence: 99%
“…There are some reports of IMS of skeletal muscles using time-of-flight (TOF)-SIMS. Magnusson et al demonstrated lipid accumulation in the skeletal muscle of leptin-deficient (ob/ob) mice by TOF-SIMS 15) , which revealed changes in the composition of monounsaturated fatty acids (FAs) and polyunsaturated FAs at high resolution. Tahellah et al also used TOF-SIMS in an attempt to visualize lipid distribution of Duchenne muscular dystrophy-affected muscles 16) .…”
Section: Application Of Ims To Skeletal Musclementioning
confidence: 99%
“…The low abundance features in the mass region m/z <700 are likely fragments of lipids or metabolites. For example, the peaks at m/z 551.5 and 577.5 have been suggested to arise from diacylglyceride molecules ([M + H − H 2 O] + ) [64,65] but could also be fragments of different classes of phospholipids with acyl chains of 32:0 and 34:1, respectively [66]. The ion at m/z 184.1 corresponds to either free phosphocholine molecules or phosphocholine fragments of PC lipids, which supports the detection of phosphatidylcholine species from the brain by LEMS.…”
Section: Matrix-free Analysis Of a Mouse Brain Section By Ti:sapphirementioning
confidence: 99%